“Evaluation of Anti-inflammatory activity of polyherbal extract of Ficus microcarpa and Adina cordifolia by Human red blood cell membrane stabilization method” (International Journal of Food and Nutritional Sciences, 2022)
Polyherbal extracts of Ficus microcarpa and Adina cordifolia were tested fortheir anti-inflammatory effects in this investigation. The in-vitro antiinflammatory effect of a polyherbal ethyl acetate extract was studied using atechnique that stabilises the membranes of human red blood cells.